SISTEM PENDUKUNG KEPUTUSAN PENENTUAN INDEKS KINERJA DOSEN DI STMIK PELITA NUSANTARA MEDAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Sinaga, Jordan; Sagal, Jijon Raphita (JURNAL SAINS DAN TEKNOLOGI, 2019)
The evaluation of lecturer performance index is an activity that is continuously carried out at universities toimprove the quality of lecturers on an ongoing basis. STMIK Pelita Nusantara will continuously evaluate the lecturerperformance index at the end of each semester, as well as to support the quality of the implementation of the tri dharmaof higher education by a lecturer plus the motivation to carry out research and community service. This study aims toobtain a computer science undergraduate level, a decision support system for assessing the lecturer performance indexusing the analytical hierarchy process (AHP) method based on 5 criteria determined by me as an element of assessmentby 1. Discipline and attendance, 2. questionnaire, 3. research, 4 devotion and 5. your attitude style. And as a dataprocessing aids used Windows 10, and MySQL as the database, and PHP programming. The results of the study areapplications with information on the results of the performance evaluation of lecturers recommended to the head of theSTMIK Pelita Nusantara Medan in carrying out the tri dharma of tertiary institutions at the end of each semester.